ANATOMICAL, HISTOLOGICAL AND RADIOLOGICAL STUDY OF THE MAMMARY GLAND OF SMALL RUMINANTS - Mahdi; A. Atyia (Basrah Journal of Veterinary Research)
Anatomical with Histological structures of the mammary gland in small ruminants [Ewe and She goat] as well as the pattern of intra mammary duct system using mammography were studies to obtain more details information about the mammary glands of small ruminants for its value in production of milk.